Study on the correlation between HSP and essential hypertension and inflammatory factors in elderly patients - Yin Yaning; Li Shubin; Dong Xingna; Wu Qian; Wu Zhenli (Guoji laonian yixue zazhi, 2025)
[Objective] To investigate the expression level of heat shock protein 90α (HSP90α) in elderly patients with essential hypertension and analyze its relationship with hypertension and inflammatory factors. [Methods] A total of 70 elderly patients with essential hypertension who underwent health check-ups at the health examination center of Inner Mongolia People’s Hospital from February 2023 to October 2024 were selected as the study group. An additional 70 healthy volunteers who underwent health check-ups during the same period were chosen as the control group. Serum HSP90α, nuclear factor κB (NF-κB), interleukin (IL) -6, tumor necrosis factor-α (TNF-α) and IL-1 levels were measured by double-antibody enzyme-linked immunosorbent assay in each group. Serum HSP90α, NF-κB, IL-6, TNF-α and IL-1 levels were compared between the two groups. Multivariate logistic regression model was used to analyze the influencing factors of elderly essential hypertension. ROC curve was used to analyze the predictive value of serum HSP90α for elderly essential hypertension. The correlation between HSP90α and inflammatory factors (IL-6, TNF-α and IL-1) and the correlation between NF-κB and inflammatory factors were analyzed. [Results] The levels of HSP90α, NF-κB, IL-6, TNF-α,IL-1 and NF-κB in the study group were higher than those in the control group (P<0.05). Multivariate logistic regression analysis showed that HSP90α, IL-6, TNF-α,IL-1 and NF-κB levels were all independent risk factors for the development of essential hypertension in the elderly (P<0.05). ROC curve analysis showed that HSP90α predicted the incidence of essential hypertension in the elderly with an area under the curve of 0.824 (95% CI: 0.757 to 0.892) and a cut-off value of 56.29 ng/mL.Spearman correlation analysis showed that serum HSP90α levels and NF-κB levels were positively correlated with IL-6, TNF-α and IL-1 levels in elderly patients with essential hypertension (P<0.05). [Conclusion] HSP90α may be involved in the occurrence of senile essential hypertension by activating chronic inflammation.